Birokrasi Dan Kebijakan Pemberantasan Tindak Pidana Korupsi: Konteks Sejarah Dan Perkembangannya Di Indonesia - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2003)
The effort to economic recovery is bogged down by rampant corruption in Indonesia. It is not only because of the bad law enforcement andjundicial system, but also because of long embedded bureaucratic culture in the country. Cultural habits have made cases of corruptions are entrenched in a hat), moral judgement. At the same time "atron-client" relationships have made it even worse. Strong leadership and commitments are needed to combat corruptions.